Water and nutrient recovery from stored urine by forward osmosis with an ammonium bicarbonate draw solution - Pocock, J.; Muzhingi, A.; Mercer, E.; Velkushnova, K.; Septien, S.; Buckley, C. A. (Frontiers in Environmental Science, 2022)
Forward osmosis with an ammonium bicarbonate draw solution was investigated as a low energy non-sewered sanitation solution, to recover nutrients and water from source separated urine. Stored urine collected from Urine Diversion Dry Toilets in the eThekwini Municipality (Durban), South Africa was used as the feed solution. Water recoveries of up to 45.9% with water fluxes up to 6.0 L m-2 h-1 were achieved using undiluted stored urine over an 8-hour operating period with a 2.5M draw solution. Rejections of up to 95% for phosphates, 85% for nitrogen and chlorides, and 75% for potassium and sodium were achieved. Low fouling of the membrane was observed after multiple runs and cleaning the membrane by circulation of deionized water or by osmotic backwash was sufficient to recover >95% of the original water flux. Little irreversible fouling was detected, assumed to be caused by carbonate calcium scaling from SEM-EDX analysis. This study suggests that forward osmosis with an ammonium bicarbonate solution could be integrated as a closed loop nutrient recycling technology for source separated urine with the prospect of clean water and draw solution recovery that could use waste heat from, for example, fecal sludge combustion.